Characterization of the nutritional quality of the meat in some species of catfish: a review / revisión: caracterización de la calidad nutricional de la carne en algunas especies de bagre (2012)
One of the most consumed fish in the world is Silurid, also called “leather fish” or catfish, whose main characteristic is the absence of intramuscular bones and scales, as well as its high productivity. In recent years, the nutritional characterization of the meat of some of these species has been carried out, finding that, although the proximal composition is within the broad ranges for fish, the fat content provides a lower proportion of polyunsaturated fatty acids (PUFA) particularly as regards omega-3 (ω-3), furthermore the ω-6/ω-3 ratio is within the proscriptions of the World Health Organization (WHO) for many of these species of catfish. Likewise, the contents of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) and amino acids, minerals and vitamins reveal a high variability between individuals and species associated with the type of cultivation and dietary habits and also with the age and weight at slaughter. Furthermore quality parameters have been defined in relation to susceptibility to autolysis, oxidation and hydrolysis of fats and disturbances caused by microorganisms that cause decisive changes in the physicochemical, microbiological and sensory characteristics. This review compiles current information regarding the nutritional composition of catfish meat and the quality parameters. / Una de las carnes de pescado de mayor consumo en el mundo es la de Silúridos, también denominados peces de cuero o bagres, cuya principal característica es la ausencia de espinas intramusculares y de escamas, además de su alta productividad. En los últimos años se ha logrado realizar la caracterización nutricional de la carne de algunas de estas especies, hallándose que aunque la composición proximal se encuentra dentro de los rangos generales para peces, el contenido de grasa ofrece menor proporción de ácidos grasos poliinsaturados (AGP) particularmente en lo referente a la serie omega 3 (ω-3), aunque la relación ω-6/ω-3 se encuentra dentro de lo establecido por la Organización Mundial de la Salud (OMS) para muchas de estas especies de bagre. De igual forma, el contenido de los ácidos eicosapentaenoico (EPA) y docosahexaenoico (DHA), así como el de aminoácidos, minerales y vitaminas, revelan una alta variabilidad individual y entre especies, asociada con el tipo de cultivo y los hábitos alimenticios, así como también con la edad y peso al momento del sacrificio. Asimismo, se han definido algunos parámetros de calidad relacionados con la susceptibilidad a la autolisis, oxidación e hidrólisis de las grasas y con las alteraciones causadas por microorganismos que generan cambios determinantes en las características fisicoquímicas, microbiológicas y sensoriales. Esta revisión recopila la información actual relacionada sobre la composición nutricional de la carne de bagre y los parámetros de calidad.